Pendampingan Redesain Saluran Irigasi di Desa Kangkung, Kabupaten Demak - Fauziyah, Shifa; Setiabudi, Bambang (Jurnal Pengabdian Vokasi, 2023)
Widening irrigation canals is important as part of the Indonesian government's efforts to increase crop yields, reduce poverty, and achieve food independence. This community service program is very much needed by the people of Kangkung Village, Demak Regency, due to the uncertain climatic conditions and the lack of adequate irrigation networks used by the community to irrigate the farmers' fields. This actual condition is the background for selecting the object of community service research to study, analyze and formulate the right irrigation channel model to help irrigate of plantation and agricultural lands for the Kangkung village community and its surroundings in order to increase the production of agricultural and plantation products.